Neural correlates linking trauma and physical symptoms - Choi, Justin J. (2022)
Highlights •Trauma patients showed greater physical health symptoms and decreased prefrontal but increased hippocampal responses to stress than controls.•More frequent physical symptoms were associated with an increased left hippocampal response to stress.•Trauma may increase physical health symptoms by compromising hippocampal function, which could also increase vulnerability to comorbid stress- and pain-related disorders.